1977
DOI: 10.2337/diab.26.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Transient Stimulatory Effect of Sustained Hyperglucagonemia on Splanchnic Glucose Production in Normal and Diabetic Man

Abstract: Insulin can modulate glucagon-stimulated hepatic glucose production and is considered to be the major factor acting in vivo to exert a couterregulatory action to glucagon. The insulin-dependent diabetic, therefore, might be especially vulnerable to enhanced hepatic glucose production promoted by glucagon. To investigate this hypothesis, low-dose glucagon infusions were administered to normal and diabetic men to compare the effects of glucagon on net splanchnic glucose production (NSGP). Four normal and three i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…We and others have previously shown that intranasally administered peptides can have metabolic effects independent of systemic absorption and plasma concentration of the hormones . Intriguingly, when administered exogenously, glucagon increases EGP transiently followed by a decline below baseline over a few hours . We therefore sought to assess the effect of 1 mg ING on plasma glucose and lipids, independent of peripheral spillover, over 6 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously shown that intranasally administered peptides can have metabolic effects independent of systemic absorption and plasma concentration of the hormones . Intriguingly, when administered exogenously, glucagon increases EGP transiently followed by a decline below baseline over a few hours . We therefore sought to assess the effect of 1 mg ING on plasma glucose and lipids, independent of peripheral spillover, over 6 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Although glucagon rapidly increases hepatic glucose output and plasma glucose concentration within 1 hour of administration, subsequently plasma glucose concentration declines to below baseline concentration, even with continuous intravenous (i.v.) glucagon infusion . A potential cause of this may be glucagon‐mediated insulin secretion .…”
Section: Introductionmentioning
confidence: 99%
“…The net effect on glucose output by the liver depends on the ratio of insulin concentration to glucagon concentration. However, the effects of glucagon appear to be short-lived and transient [23,24].…”
Section: Protein Metabolism and Regulationmentioning
confidence: 93%
“…There was no plasma cyclic AMP response to a glucagon infusion, suggesting down-regulation of the glucagon receptor by the chronic hyperglucagonaemia. Post-operatively the hepatic glucose production and clearance rate of glucose fell, whereas the plasma cyclic AMP responses to the glucagon infusion reverted to a normal pattern.It is concluded that chronic hyperglucagonaemia is not a major factor in the development of the glucose intolerance, but it may lead to down-regulation of the biological action of glucagon.From studies employing the acute administration of somatostatin in man and experimental animals, it has been concluded that glucagon plays a major role in maintaining basal hepatic glucose production (HGP) (Alford et al, 1974; Cherrington et al, 1976;Liljenquist et al, 1977). Furthermore, it has been shown that glucagon excess can lead to…”
mentioning
confidence: 99%
“…From studies employing the acute administration of somatostatin in man and experimental animals, it has been concluded that glucagon plays a major role in maintaining basal hepatic glucose production (HGP) (Alford et al, 1974; Cherrington et al, 1976;Liljenquist et al, 1977). Furthermore, it has been shown that glucagon excess can lead to…”
mentioning
confidence: 99%